PERBANDINGAN SIMAYANG TIPE II DENGAN PROBLEM SOLVING TERHADAP EFIKASI DIRI DAN PENGUASAAN KONSEP - Irma Soleha; Sunyono Sunyono; Emmawaty Sofya (Universitas Lampung, 2015)
The quasi-experimental research has been done in SMA Negeri 16 Bandar Lampung with non equivalent control group design. This research was aimed to disccribe comparison results between the SiMaYang type II and problem solving learning model to improve students self-efficacy and concept mastery on topic of electrolyte and non electrolyte solution. The determination of sample class has been done by using cluster random sampling and it was obtained 10th grade-1 as the 1st experiment class and 10th grade-3 as the 2nd experiment class. The comparison result both of these learning model was indicated from students self- efficacy and concept mastery, students activity during implementation of learning model, and students responses to the implementation of learning models. The research result showed that students self-afficacy and concept mastery which use SiMaYang type II learning model was better than use problem solving learning model.Penelitian kuasi eksperimen telah dilakukan di SMA Negeri 16 Bandar Lampung dengan non equivalent control group design. Penelitian ini bertujuan untuk mendeskripsikan perbandingan model pembelajaran SiMaYang tipe II dan problem solving dalam meningkatkan efikasi diri dan penguasaan konsep siswa pada materi larutan elektrolit dan non-elektrolit. Pengambilan sampel dilakukan dengan cara cluster random sampling dan diperoleh kelas X1 sebagai kelas eksperimen I dan kelas X3 sebagai kelas eksperimen II. Perbandingan kedua model pembelajaran ini ditentukan oleh efikasi diri dan penguasaan konsep siswa, aktivitas siswa selama pembelajaran berlangsung, dan respon siswa terhadap pelaksanaan pembelajaran. Hasil penelitian menunjukkan bahwa efikasi diri dan penguasaan konsep siswa menggunakan model pembelajaran SiMaYang tipe II lebih baik dibandingkan dengan menggunakan model pembelajaran problem solving.